2020
DOI: 10.4018/978-1-7998-0186-3.ch006
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Blockchain in Stock Market

Abstract: Blockchain is one of the growing technologies used for financial management systems. Financial data must be kept secure otherwise it can create a huge loss. So, whenever security features or technologies are developed must keep financial security as a priority. Stock market management is another area of finance sector that works on two concepts, that is, minimize the risk and maximize the profit. In this chapter, the authors discuss how blockchain technology is used for stock market analysis. Mainly blockchain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Because the UAE banking industry has been an early adopter of blockchain technology, it reduces costs, speeds transactions, improves data quality, accepts electronic currencies, improves accountability, improves compliance and ultimately improves performance, which, in turn, reflects on stock prices. The results of this study are in line with previous research, such as that of Guo and Liang (2016), Arjun and Suprabha (2020) and Nair and Bhagat (2020), which found that cost optimization, increased operational efficiency and risk reduction were among the factors that led to the adoption of these technologies in banking industry.…”
Section: Findings and Data Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Because the UAE banking industry has been an early adopter of blockchain technology, it reduces costs, speeds transactions, improves data quality, accepts electronic currencies, improves accountability, improves compliance and ultimately improves performance, which, in turn, reflects on stock prices. The results of this study are in line with previous research, such as that of Guo and Liang (2016), Arjun and Suprabha (2020) and Nair and Bhagat (2020), which found that cost optimization, increased operational efficiency and risk reduction were among the factors that led to the adoption of these technologies in banking industry.…”
Section: Findings and Data Analysissupporting
confidence: 91%
“…Based on the mean equation as illustrated in Table 4, the findings indicate that blockchain technology has a significant positive influence on the stock market returns of both Abu Dhabi and Dubai banks. Because the UAE banking industry has been an early Guo and Liang (2016), Arjun and Suprabha (2020) and Nair and Bhagat (2020), which found that cost optimization, increased operational efficiency and risk reduction were among the factors that led to the adoption of these technologies in banking industry.…”
Section: Symmetric Volatility Analysis Resultsmentioning
confidence: 99%
“…Data from decentralised data sources provides more and safer data from both internal and external sources. In sources of intrinsic data for local and metropolitan areas, the data from a certain company's branch might be stated to be local [ 29 , 30 ]. Combined data from different companies' metropolitan data is represented by branches.…”
Section: Background and Related Workmentioning
confidence: 99%
“…While several financial services companies, such as Deutsche KfW Financial Institutions, are still performing simulations for blockchain-enabled securities trading, others have fully integrated blockchain technology into secondary market services. A good example is the Nasdaq Linq [97], a PE trading solution developed by Nasdaq in collaboration with the blockchain start-up Chain.com [82]. This platform enables non-listed users to transfer their equity and perform a PE transaction's settlement.…”
Section: Secondary Market Statusmentioning
confidence: 99%